Distinct characteristics of western Pacific atmospheric rivers affecting Southeast Asia - Yong, Yangyang; Liang, Ju; Yang, Kai (Frontiers in Marine Science, 2023)
The dynamic characteristics of atmospheric rivers (ARs) have been researched over the western North Pacific and East Asia due to their close linkage to disastrous precipitation extremes, while very little attention has been paid to the AR features from the western Pacific to Southeast Asia. This study aims to quantify the climatology, long-term trends and variability of different AR properties from the western Pacific to Southeast Asia using an objective identification algorithm, the ERA5 reanalysis dataset and the APHRODITE precipitation dataset for the period 1951-2015. The results indicate a belt of frequent AR activities from the western Pacific to the Andaman Sea during the boreal autumn-winter season. The long-term trend analyses show a significantly increasing trend in AR frequency and an eastward shift of AR plumes. These dynamic changes contribute to the increasing trend of extreme precipitation amounts in the coastal areas surrounding the South China Sea. The intraseasonal variability of the AR associated with the Madden-Julian oscillation (MJO) shows a pronounced enhancement of AR activity in the MJO phase-2 to phase-3 due to the steeper gradient of low-level geopotential height between the Northwestern Pacific and the tropical Indian Ocean. The modulation is partly explained by the enhanced MJO convection and the adiabatic heating in the vicinity of the trough of the 200-500 hPa geopotential thickness of the region. This study shows that ARs are important mechanisms behind the climatology, trends and variability of the regional precipitation in Southeast Asia. This study implies that more attention is required toward the dynamics of these tropical weather systems, particularly for their interactions with other synoptic processes and their response to future climate warming.